A Cluster of Transverse Myelitis Following Dengue Virus Infection in the Brazilian Amazon Region - de Sousa, Adriano Miranda (The Japanese Society of Tropical Medicine, 2014)
Background and Purpose: During the last two decades, clinical reports have begun to place increasing emphasis on the possible neurological complications related to dengue. However, reports of cases with myelitis post dengue are rare. This study describes an unprecedented cluster of transverse myelitis following a dengue virus infection. Methods: 51 possible cases of neurological complications related to dengue were identified by the epidemiological surveillance of the State of Rondônia, Brazil and submitted to serial neurological examination, electromyography, vertebral MR and laboratory investigation to confirm the dengue diagnosis and rule out other arboviruses. Results: The diagnosis of acute transverse myelitis post-dengue was established in 26 patients, the majority were women, young and white. Antibodies against virus IgM were present in all cases and DEN 3 virus was isolated by PCR in one patient. Treatment with IV steroids was useful. Conclusions: The cluster of transverse myelitis post-dengue with favorable clinical outcome here reported suggests an immune mediated mechanism for the spinal cord involvement. Whereas dengue epidemics are frequent in tropical and subtropical countries, the dengue fever should be part in the differential diagnosis of the infectious and post-infectious myelitis.